From bonding to action: The influence of generalized and interpersonal trust on voluntary membership among European adults - Julia Sánchez-García; Marta Gil-Lacruz; Ana Isabel Gil-Lacruz; Miguel Ángel Cañete-Lairla (PLoS ONE, 2025)
This study examines the moderating role of social trust (generalized and particularized/interpersonal) at the national level on the relationship between age (middle-aged 45–59 years; older adults 60–74 years; and long-lived 75 years and older) and membership in voluntary organizations in general and of various types. We hypothesize that in all three age groups, people in countries with higher levels of general and specific trust are more likely to engage in volunteer activities. At the same time, participation in volunteer activities is expected to decline gradually with age. The sample comprises individuals over 45 years of age ( N = 28,198) in 36 countries in Europe. The empirical estimation uses data from the 2017/22 European Values Survey. Multilevel analysis is used to allow hierarchical aggregation of variables from different levels: individual, national and welfare system. The study reveals that generalized trust is positively associated with volunteering membership among people aged 45 and older. However, it is interpersonal trust that is positively related to voluntary membership among people aged 75 years and older. Furthermore, the influence of the two types of trust varies according to the type of membership. The research highlights that although public and social policies in recent years have promoted the voluntary activity of older adults, not all ages are the same; each age group has a series of characteristics that must be taken into consideration for such an increase in volunteering to take place at all ages.